1983
DOI: 10.4102/sajp.v39i3.888
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and motivation

Abstract: A short history of the use of exercise in Medicine is given. This is followed by the neurophysiological basis of exercise and its physical and psychological effects on motivation in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The bleaching of the sandstone through removal of iron(III) oxide probably assists the detachment of quartz grains and helps in the achievement of the weathering effects. 32 Optical and SEM studies 29 have demonstrated that lichen hyphae penetrate the sandstone pores to a depth of ¾1.5 mm below the surface with localized penetration to greater depths. Detachment of the quartz grains in the bioweathered substratum can result in an incorporation of˛-quartz into the lichen thalli.…”
Section: Resultsmentioning
confidence: 99%
“…The bleaching of the sandstone through removal of iron(III) oxide probably assists the detachment of quartz grains and helps in the achievement of the weathering effects. 32 Optical and SEM studies 29 have demonstrated that lichen hyphae penetrate the sandstone pores to a depth of ¾1.5 mm below the surface with localized penetration to greater depths. Detachment of the quartz grains in the bioweathered substratum can result in an incorporation of˛-quartz into the lichen thalli.…”
Section: Resultsmentioning
confidence: 99%